Preparation method of quinoline amino binuclear metal titanium zirconium hafnium catalyst and application of catalyst in olefin polymerization

By constructing a quinoline amino-based binuclear metal titanium zirconium hafnium catalyst, the problem of the activity and molecular weight of polyolefin at high temperature is solved by utilizing the binuclear metal synergistic effect and catalyst structural characteristics, and the effect of efficient synthesis of high-molecular polyolefin elastomers and random propylene is achieved.

CN119529141APending Publication Date: 2025-02-28QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411751696.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

At high temperatures, the activity of the polyolefin catalyst and the molecular weight of the generated polymer will usually decrease, making it difficult to effectively synthesize high molecular weight polyolefin elastomers.

Method used

By introducing rigid anthracene as the skeleton of bridged binuclear metal, a quinoline amino-based binuclear metal titanium zirconium hafnium catalyst is constructed, and the molecular weight of the polymer is improved by utilizing the synergistic effect of the binuclear metal and the steric hindrance and electron effects of the catalyst structure.

Benefits of technology

It has achieved efficient synthesis of polyolefin elastomers and ultra-high molecular weight random propylene at high temperatures, with excellent catalytic activity and excellent high temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165160640000031
    Figure BDA0005165160640000031
  • Figure BDA0005165160640000032
    Figure BDA0005165160640000032
  • Figure BDA0005165160640000061
    Figure BDA0005165160640000061
Patent Text Reader

Abstract

In the invention, rigid anthracene is introduced as a framework of bridged binuclear metal, the quinoline amino binuclear metal titanium zirconium hafnium catalyst is constructed, and the molecular weight of the obtained polymer can be effectively improved through the synergistic effect between the binuclear metal and the steric hindrance and electronic effect on the catalyst structure; a polyolefin elastomer (POE) and an ultra-high molecular weight random propylene (UHMWaPP) elastomer are efficiently synthesized. The quinoline amino binuclear metal titanium zirconium hafnium catalyst has the advantages of simple synthesis, easily available raw materials and high product yield. In copolymerization of ethylene and alpha-olefin, the catalyst shows excellent activity (6.25 * 10 < 7 > g (POE). Mol <-1 > (M). H <-1 >) and alpha-olefin selectivity (the insertion rate reaches 29.2 mol%), and a high-molecular-weight polyolefin elastomer (POE) (the polymer molecular weight Mw reaches 925 kg.mol <-1 >) is prepared. In propylene polymerization, the regularity of the polypropylene chain segment can be effectively regulated and controlled by adjusting the steric hindrance and the electronic effect of the catalyst, and the atactic polypropylene elastomer with the ultra-high molecular weight (the molecular weight reaches 3250 kg.mol <-1 >) is prepared with the high activity (6.6 * 10 < 7 > g (PP). Mol <-1 > (M). H <-1 >). In addition, the quinoline amino binuclear metal titanium zirconium hafnium catalyst also shows excellent high temperature resistance (higher than 160 DEG C), is suitable for high-temperature solution polymerization, and can be used for preparing high-performance polyolefin elastomers. Therefore, the invention has original innovation, and provides a new direction for the development of the field of polyolefin materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of olefin coordination polymerization metal catalyst and its application in the field of olefin polymerization. Background Art

[0002] In recent years, the production capacity and application scope of polyolefin materials have continued to grow. Polyolefin materials such as polyethylene (PE), polypropylene (PP) and ethylene / α-olefin copolymers are widely used in many fields of daily life and defense industry due to their light weight, high mechanical strength, excellent impact resistance and outstanding processability.

[0003] With the continuous development of society, the demand for high-performance polyolefins continues to increase. Among them, polyolefin elastomer (POE) is a random copolymer formed by copolymerization of ethylene and 1-octene, 1-hexene or 1-butene. When the content of higher α-olefins in the copolymer is high (usually more than 20wt.%), it is a semi-crystalline, low-modulus polymer with excellent mechanical and elastic properties. It has attracted much attention in the automotive industry and photovoltaic film fields. Ultra-high molecular weight random polypropylene (UHWMaPP) is a special type of elastomer with a molecular weight of millions and a linear structure. It has the characteristics of low hardness and high elongation. By adjusting the isotactic content of polypropylene between 90% and 10%, the performance of the resin material can be adjusted from high rigidity to high flexibility. Because it can overcome the shortcomings of low strength of medium and low molecular weight random polypropylene, ultra-high molecular weight random polypropylene

[0004] (UHWMaPP) elastomers are expected to be used in some special material fields. However, under normal polymerization conditions, only random polypropylene with a molecular weight of several hundred thousand can be obtained, and the preparation of ultra-high molecular weight random polypropylene (UHWMaPP) elastomers is a huge challenge.

[0005] Generally speaking, polyolefin elastomers are synthesized by solution polymerization technology, which can produce more efficient products and better control the polymer microstructure, thus obtaining materials with better performance. Solution polymerization is best carried out at high temperature (usually above 120°C) to prevent the polymer from precipitating during the polymerization process. In addition, high temperature solution polymerization can reduce viscosity and increase product yield, thereby reducing costs. However, these limitations pose great challenges to the catalysts used to catalyze olefin polymerization, because the activity of polyolefin catalysts and the molecular weight (Mws) of the resulting polymers generally decrease with increasing polymerization temperature. Therefore, it is very necessary to develop homogeneous metal catalysts with better catalytic performance at high temperatures.

[0006] For this reason, researchers around the world have designed and synthesized metallocene and constrained geometry catalysts (CGC), and have been successfully used in the commercial production of polyolefin elastomer POE since the early 1990s (Chem. Rev. 1998, 98, 2587-2598). In addition, many non-metallocene transition metal catalysts have also gradually developed. Kloin et al. improved the high temperature resistance of the catalyst by introducing quinoline structure, and obtained a series of metal catalysts with different catalytic properties by changing the substituents of the catalyst structure (Organometallics 2013, 31, 6244-6251). Liu et al. prepared quinoline-amine metal catalysts, which can maintain high activity and high α-olefin insertion rate under high temperature conditions (Organometallics 2024, 43, 2472-2479). Although quinoline amine ligands can provide good high temperature resistance and copolymerization performance for metal catalysts, they do not significantly improve polymer molecular weight.

[0007] In the present invention, rigid anthracene is introduced as the skeleton of the bridging binuclear metal to construct a quinoline amine binuclear metal titanium zirconium hafnium catalyst. Through the synergistic effect of binuclear metals and the steric hindrance and electronic effects of the catalyst structure, the molecular weight of the obtained polymer can be effectively increased, and polyolefin elastomers (POE) and ultrahigh molecular weight random propylene (UHMWaPP) elastomers can be efficiently synthesized. The quinoline amine binuclear metal titanium zirconium hafnium catalyst reported in the present invention has the advantages of simple synthesis, easy raw materials and high product yield. In the copolymerization of ethylene and α-olefins, the catalyst exhibits excellent activity (6.25×10 7 g(POE)·mol -1 (M) ·h -1 ), α-olefin selectivity (insertion rate up to 29.2 mol%), preparation of high molecular weight polyolefin elastomer POE (polymer molecular weight Mw up to 925 kg·mol -1 In propylene polymerization, the regularity of polypropylene chain segments can be effectively regulated by adjusting the catalyst steric hindrance and electronic effect, with high activity (6.6×10 7 g(PP)·mol -1 (M) ·h -1 ) to prepare ultra-high molecular weight (molecular weight up to 3250kg·mol -1) random polypropylene elastomer. In addition, the quinolineamino binuclear metal titanium zirconium hafnium catalyst reported in the present invention also exhibits excellent high temperature resistance (greater than 160°C), is suitable for high temperature solution polymerization, and can prepare high-performance polyolefin elastomers. As a comparison, the quinoline amino binuclear metal titanium zirconium hafnium catalyst reported in the present invention shows better catalytic effect than the NN two-dentate coordination hafnium metal catalyst Hf1 (2,6-diisopropylphenyl) (8-quinolinyl-amido) HfMe3) (Organometallics 2012, 31, 6244-6251), Hf2 (2,6-diisopropylphenyl) (8-trihydroquinolinyl-amido) HfMe3) (Organometallics 2021, 40, 242-252), Hf3 (2,6-diisopropylphenyl) (2-quinolinyl-amido) HfMe3) (Organometallics 2024, 43, 2472-2479), and the mononuclear hafnium metal Hf4 (1-N-anthracenyl- (2-quinolinyl-amino) HfMe3) catalyst. Therefore, the present invention is original and innovative, and provides a new direction for the development of the field of polyolefin materials. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a quinolineamine binuclear metal titanium zirconium hafnium catalyst and its application in olefin polymerization to prepare polyolefin elastomer POE and ultrahigh molecular weight random propylene (UHMWaPP) elastomer.

[0009] The present invention provides a quinolineamino binuclear metal titanium zirconium hafnium catalyst represented by formula (I):

[0010]

[0011] Wherein, M is selected from titanium, zirconium, and hafnium; R 1 -R 4 , R 1’ -R 4’ Each independently selected from hydrogen, C1-C 20 Alkyl, C1-C 20 Alkoxy, C6-C 20 Aryl, C6-C 20 Aralkyl, or any two adjacent carbon atoms of phenyl and the surrounding substituents form a ring containing 4-20 carbon atoms; R 1’ -R 4’ R 1 -R 4 Same or Different; R 5, R 5’ Each is independently selected from a C1-C6 straight chain alkyl group, a tert-butyl group, a phenyl group, a benzyl group, or an isopropylphenyl group.

[0012] Preferably, the quinolineamino binuclear metal titanium zirconium hafnium catalyst of the present invention is selected from any one of the metal catalysts shown in (II):

[0013]

[0014] The present invention provides a method for preparing the above-mentioned quinolineamino binuclear metal titanium zirconium hafnium catalyst, comprising the following steps:

[0015] Under a nitrogen atmosphere, the metal salt is dissolved in 20-80 mL of anhydrous solvent, 4.0-5.0 molar equivalents of methylmagnesium bromide are added, and the reaction is carried out at -40°C to -20°C for 2-6 hours, and then 0.5 molar equivalents of a difunctional quinoline imine ligand are added, and the reaction is carried out at -40°C to -20°C for 2-6 hours, and then the temperature is raised to room temperature and the reaction is carried out for 2-12 hours; after the reaction is completed, the solvent is removed under reduced pressure, and extraction is carried out with a good solvent to obtain the quinoline amino binuclear metal titanium zirconium hafnium catalyst according to claim 1.

[0016] In the above preparation method, the anhydrous solvent is selected from toluene, n-hexane, xylene, and benzene; and the good solvent is selected from n-hexane, toluene, pentane, heptane, and cyclohexane.

[0017] In the above preparation method, the metal salt is selected from one of TiCl4, ZrCl4, and HfCl4.

[0018] The present invention also provides the use of the quinolineamino binuclear metal titanium zirconium hafnium catalyst in catalyzing olefin polymerization.

[0019] In the above application, the olefin monomer is one or more of ethylene, propylene, 1-butene, styrene, 1-hexene, 1-octene, and 1-decene.

[0020] In the above polymerization reaction, the quinoline amine-based binuclear metal titanium zirconium hafnium catalyst needs to be catalyzed with a co-catalyst, and the co-catalyst is one or more of tris-pentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl) borate, aluminoxane, alkyl aluminum, and alkyl aluminum chloride. The aluminoxane is methylaluminoxane, ethylaluminoxane or isobutylaluminoxane; the alkyl aluminum is trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; the alkyl aluminum chloride is diethylaluminum monochloride, diethylaluminum sesquichloride or ethylaluminum dichloride.

[0021] In the above polymerization reaction, the polymerization temperature is 0-200°C, the polymerization pressure is 0.1-5MPa, the molar ratio of the catalyst to the co-catalyst is 1:(1-5000), the reaction time is 0.1-48h, and the polymerization solvent is one or more of n-hexane, n-heptane, n-pentane, and toluene.

[0022] The present invention provides the preparation of a quinoline amine-based binuclear metal titanium zirconium hafnium catalyst, and the use of the catalyst in catalyzing olefin polymerization to prepare polyolefin elastomers POE and ultrahigh molecular weight random propylene (UHMWaPP) elastomers. The quinoline amine-based binuclear metal titanium zirconium hafnium catalyst reported in the present invention has the advantages of simple synthesis, easy availability of raw materials, and high product yield. It has high catalytic activity in the copolymerization of ethylene and α-olefins (the activity can reach up to 6.25×10 7 ·mol -1 ·h -1 ) and better copolymerization performance (1-octene insertion rate can reach 29.2 mol%); in propylene polymerization, the regulation of steric hindrance of different substituents can be highly efficient (activity can reach up to 6.6×10 7 g·mol -1 ·h -1 ) Synthesized ultra-high molecular weight random polypropylene (UHMWaPP) elastomer (polymer molecular weight up to 3250 kg·mol -1 ); especially in high-temperature solution polymerization, the catalyst still maintains excellent polymerization performance to prepare high-quality, high-performance polyolefin materials. The quinoline amine-based binuclear metal titanium zirconium hafnium catalyst provided by the present invention is original and innovative and can promote the development of my country's high-end polyolefin chemical industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the H NMR spectrum of catalyst C1.

[0024] Figure 2 This is the nuclear magnetic carbon spectrum of polyolefin elastomer POE with a 1-octene insertion rate of 6.5 mol%.

[0025] Figure 3 This is the nuclear magnetic carbon spectrum of polyolefin elastomer POE with a 1-octene insertion rate of 18.8 mol%.

[0026] Figure 4 The molecular weight is 325×10 4 g·mol -1 GPC spectrum of ultra-high molecular weight random polypropylene elastomer.

[0027] Figure 5 The molecular weight is 223×10 4 g·mol -1 GPC spectrum of ultra-high molecular weight random polypropylene elastomer.

[0028] Figure 6 It is the DSC curve of ultra-high molecular weight random polypropylene elastomer.

[0029] Figure 7 This is the NMR carbon spectrum of ultra-high molecular weight random polypropylene elastomer with a regularity of 18.5mmmm%.

[0030] Figure 8 This is the WAXD curve of ultra-high molecular weight random polypropylene elastomer.

[0031] Fig. 9 This is the tensile cycle curve of the elastic recovery experiment of ultra-high molecular weight random polypropylene elastomer.

[0032] Fig.10 This is a crystal diagram of catalyst C1. DETAILED DESCRIPTION

[0033] The present invention is further described by way of examples, but the present invention is not limited thereto. The examples of the present invention can enable those skilled in the art to understand the present invention more comprehensively.

[0034] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0035] The bifunctional quinolinylamine ligands C1-L, C2-L and C4-L in the present invention are shown in (III), and the corresponding synthesis methods are given in Examples 1, 2 and 3. The mononuclear metal catalysts used in the control experiment are shown in (IV), Hf1(2,6-diisopropylphenyl)(8-quinolinyl-amido)HfMe3; Organometallics 2012, 31, 6244-6251), Hf2(2,6-diisopropylphenyl)(8-trihydroquinolinyl-amido)HfMe3; Organometallics 2021, 40, 242-252), and Hf3(2,6-diisopropylphenyl)(2-quinolinyl-amido)HfMe3; Organometallics 2024, 43, 2472-2479) are synthesized according to the literature method. The corresponding synthesis method of the mononuclear hafnium metal Hf4 (1-N-anthracenyl-(2-quinolinyl-amino)HfMe3) catalyst used in the control experiment is given in Example 5.

[0036]

[0037] The present invention is described below with reference to specific embodiments.

[0038] Example 1. Preparation of Catalyst C1

[0039] Weigh 1,8-diaminoanthracene (0.416 g / 2 mmol) and 2-quinolinealdehyde (0.69 g / 4.4 mmol) into a round-bottom flask, add 20 mL of anhydrous ethanol, add 2 mg of p-toluenesulfonic acid as a catalyst, react at room temperature for 6 hours, and filter the obtained yellow suspension. Wash with a small amount of ice ethanol to obtain 0.67 g of yellow-green ligand powder C1-L with a yield of 82%. 1 H NMR (400MHz, CDCl3): δ9.57(s,1H),8.98(s,2H),8.60(d,J=8.5Hz,2H),8.50(s,1H),8.20(d,J=8.4Hz,2H),8.16(d,J=8.5Hz,2H),7.99(d, J=8.1Hz,2H),7.91(d,J=8.2Hz,2H),7.82–7.78(m,2H),7.58–7.50(t,J=8.1Hz,J=8.2Hz,2H),7.56–7.52(m,2H),7.24(d,J=7.0Hz,2H)ppm. 13 CNMR (100MHz, CDCl3): δ160.98,155.36,148.71,148.23,136.55,132.65,130.16,130.06, 129.07,127.97,127.86,127.78,127.12,126.06,119.74,119.03,111.71ppm.Anal.Calcd for C 34 H 22 N4:C,83.93;H,4.56;N,11.51.Found:C,83.94;H,4.63;N,11.43.HRMS Calcd.for[M+H + ]487.5860,Found:487.5862.

[0040] Weigh hafnium tetrachloride (0.352g, 1.1mmol), add 10mL of anhydrous toluene, slowly add 1.6mL / 4.8mmol of methylmagnesium bromide solution (3M) at -40℃ (acetonitrile-liquid nitrogen cold bath), and stir for 2 hours. Then add ligand C1-L (0.259g / 0.5mmol), react at -40℃ in the dark for 2 hours, and continue to react at room temperature for 5 hours. After the reaction, remove the solvent, extract with toluene, and filter to obtain 0.33g of product with a yield of 69%. 1H NMR (400MHz, C6D6): δ9.57 (s, 1H), 8.98 (s, 2H), 8.60 (d, J = 8.5Hz, 2H), 8.50 (s, 1H),8.20(d,J=8.4Hz,2H),8.16(d,J=8.5Hz,2H),7.99(d,J=8.1Hz,2H),7.91( d,J=8.2Hz,2H),7.82–7.78(m,2H),7.58–7.50(t,J=8.1Hz,J=8.2Hz,2H),7.56 –7.52(m,2H),4.9(q,2H),1.56(d,J=8.4Hz,6H),0.88(s,9H),0.80(s,9H)ppm. 13 C NMR (100MHz, CDCl3): δ160.98,155.36,148.71,148.23,136.55,132.65,130.16,130.06,129.07,127.9 7,127.86,127.78,127.12,126.06,119.74,119.03,111.71,56.49,56.43,19.51,17.22ppm.Anal.Calcd for C 42 H 46 Hf2N4:C,52.34;H,4.81;N,5.81.Found:C,52.40;H,4.76;N,5.80.

[0041] Example 2. Preparation of Catalyst C2

[0042] Weigh the corresponding C1-L ligand (0.486 g / 1 mmol) into a bottle, evacuate and replace with nitrogen three times, add 20 mL of anhydrous ether, slowly add 3 equivalents of tert-butyl lithium (3 mL / 1 M in Hex) under a nitrogen atmosphere, and stir at room temperature for 2 hours. Add 1 M NH4Cl aqueous solution to quench, add ethyl acetate to extract, remove the upper organic layer, dry, and remove the solvent under low pressure to obtain 0.47 g of yellow solid product C2-L with a yield of 78%. 1HNMR(400MHz, CDCl3)δ9.29(d,J=0.8Hz,1H),8.92(d,J=7.4Hz,2H),8.24(s,1H),8.03–7.98(m,2H),7.98–7.93(m,2H),7.75–7.66(m, 4H),7.55–7.46(m,4H),7.35(d,J=8.0Hz,2H),7.02(dd,J=8.3,1.3Hz,2H),5.50(d,J=9.1Hz,2H),4.98–4.92(m,2H),1.07(s,18H)ppm. 13 C NMR (100MHz, CDCl3) δ158.33,148.18,144.78,134.99,132.40,129.36,128.97,127.79,127.71,1 27.35,126.24,126.18,123.67,123.45,123.40,118.76,113.71,70.39,35.15,26.78.Anal.Calcd for C 44 H 42 N4:C,83.68;H,7.02;N,9.29.Found:C,83.54;H,4.83;N,5.87.

[0043] Weigh hafnium tetrachloride (0.352g, 1.1mmol), add 10mL dry toluene, slowly add 1.6mL / 4.8mmol methylmagnesium bromide solution (3M) at -40℃ (acetonitrile-liquid nitrogen bath), and stir for 2 hours. Then add ligand C2-L (0.308g / 0.5mmol), stir for two hours at -40℃ in the dark, and continue to react for 5 hours after returning to room temperature. After the reaction is completed, remove the solvent, extract with toluene, and filter to obtain 0.37g of product with a yield of 70%. 1 H NMR(400MHz,C6D6)δ8.33(s,1H),8.32–8.30(m,2H),8.20(s,1H),7.88–7 .84(m,3H),7.83(s,2H),7.76(d,J=8.0Hz,2H),7.52–7.44(m,4H),7.41–7 .38(m,2H),7.30(dd,J=7.4,1.4Hz,2H),7.25(t,J=7.7,1.1Hz,2H),4.27 (t,J=1.4Hz,2H),1.07(s,9H),1.05(s,9H),0.98(s,9H),0.93(s,9H)ppm. 13C NMR (100MHz, C6D6) δ162.90,149.29,136.81,134.24,132.41,131.04,128.47,128.13,127.90,127.57,127.55,127.18, 126.20,125.00,123.85,120.27,119.25,72.49,41.17,41.15,19.04,19.01,18.99,18.97,18.94,18.92ppm.Anal.Calcd for C 48 H 58 Hf2N4:C,55.01;H,5.58;N,5.35.Found:C,55.09;H,5.53;N,5.32.

[0044] Example 3. Preparation of Catalyst C3

[0045] Weigh zirconium tetrachloride (0.256 g, 1.1 mmol), add 10 mL of dry toluene, slowly add 1.6 mL / 4.8 mmol of methylmagnesium bromide solution (3 M) at -40 °C (acetonitrile-liquid nitrogen bath), and stir for 2 hours. Then add ligand C1-L (0.259 g / 0.5 mmol), stir for 2 hours at -40 °C in the dark, and return to room temperature to continue the reaction for 5 hours. After the reaction is completed, remove the solvent, extract with toluene, and filter to obtain 0.284 g of product with a yield of 72%. 1 H NMR(400MHz,C6D6)δ9.52(s,1H),8.52–8.46(m,2H),8.37(s,1H),8.04(d, J=8.9Hz,2H),7.92(dt,J=8.2,0.8Hz,2H),7.83–7.77(m,2H),7.75–7.69(m ,2H),7.56(t,J=8.0,7.6Hz,2H),7.46–7.37(m,2H),7.22–7.17(m,2H),6.7 9(s,2H),4.60(q,2H),1.50(d,J=8.3Hz,6H),0.53(s,9H),0.41(s,9H)ppm. 13CNMR(100MHz,C6D6)δ148.28,148.26,141.62,137.73,137.10,137.08,132.88,128.77,128.72,128.15,127.90,12 7.82,127.54,126.20,125.19,124.64,123.80,120.74,119.25,56.38,56.33,20.55,19.97,19.81ppm.Anal.Calcd for C 42 H 46 Zr2N4:C,63.91;H,5.87;N,7.10.Found:C,63.97;H,5.82;N,7.08.

[0046] Example 4. Preparation of Catalyst C4

[0047] Weigh 1,8-diaminoanthracene (0.416g / 2mmol) and 8-methoxyquinoline-2-carboxaldehyde (0.823g / 4.4mmol) in a round-bottom flask, add 20mL of anhydrous ethanol, add 2mg of p-toluenesulfonic acid as a catalyst, react at room temperature for 6 hours, obtain a yellow suspension, filter it, and rinse it with a small amount of ice ethanol to obtain a yellow-green intermediate product. Weigh the corresponding intermediate product (0.548g / 1mmol) in a bottle, evacuate and replace it with nitrogen three times, add 20mL of anhydrous ether, slowly add 3 equivalents of 2-isopropylphenyl lithium salt (0.378g / 3mmol) in ether solution under nitrogen atmosphere, and stir at room temperature for 2 hours. Add 1M NH4Cl aqueous solution to quench, add ethyl acetate to extract, remove the upper organic layer, dry, and remove the solvent under low pressure to obtain 0.535g of yellow solid product C4-L with a yield of 71%. 1 H NMR(400MHz, CDCl3)δ9.72(s,1H),8.97–8.73(m,2H),8.61(s,1H),7.74–7.69(m,2H) ),7.61–7.54(m,6H),7.44(t,J=8.4Hz,2H),7.36–7.27(m,2H),7.23(t,J=8.0,1.4Hz ,2H),7.20–7.15(m,4H),7.07–6.95(m,4H),6.56(d,J=7.9,2H),5.89(d,J=7.9Hz,2 H),3.22–3.11(m,2H),2.70(s,6H),1.28(d,J=6.8Hz,6H),1.23(d,J=6.6Hz,6H)ppm. 13C NMR (100MHz, CDCl3) δ160.99,147.56,146.92,143.24,137.46,135.44,134.92,132.39,130.57,128.81,128.72,127.72,127. 71,127.49,127.30,126.18,126.02,125.89,124.28,123.67,121.69,118.65,113.40,61.81,29.55,23.51,18.02.Anal.Calcd forC 54 H 50 N4O2:C,82.41;H,6.40;N,7.12.Found:C,82.33;H,6.43;N,7.36.

[0048] Weigh hafnium tetrachloride (0.352g, 1.1mmol), add 10mL dry toluene, slowly add 1.6mL / 4.8mmol methylmagnesium bromide solution (3M) at -40℃ (acetonitrile-liquid nitrogen bath), and stir for 2 hours. Then add ligand C4-L (0.378g / 0.5mmol), stir for two hours at -40℃ in the dark, and continue to react for 5 hours after returning to room temperature. After the reaction is completed, remove the solvent, extract with toluene, and filter to obtain 0.324g of product with a yield of 54%. 1 H NMR(400MHz,C6D6)δ9.52(s,1H),7.90–7.81(m,2H),7.65(s,1H),7.49– 7.40(m,2H),,7.30–7.16(m,10H),6.99(t,J=1.5,0.8Hz,2H),6.88–6.81 (m,2H),5.77–5.69(m,2H),3.26–3.15(m,2H),2.49(d,J=0.7Hz,6H),1. 28(d,J=6.6Hz,6H),1.23(d,J=6.7Hz,6H),0.81(s,9H),0.79(s,9H)ppm. 13CNMR(100MHz,C6D6)δ151.88,151.82,147.43,147.40,146.32,140.24,139.57,138.14,137.01,132.44,130.36,128.57,128.53,128.08,1 27.89,127.48,127.09,126.13,125.96,125.80,123.84,121.67,119.24,61.96,61.92,29.34,23.51,18.98,18.95,18.90.ppm.Anal.Calcd for C 60 H 66 Hf2N4O2:C,58.49;H,5.40;N,4.55.Found:C,58.15;H,5.47;N,4.64.

[0049] Example 5. Preparation of Catalyst Hf4

[0050] Weigh 1-aminoanthracene (0.386 g / 2 mmol), 2-quinolinealdehyde (0.35 g / 2.2 mmol) and 2 mg of p-toluenesulfonic acid in a round-bottom flask, add 20 mL of anhydrous ethanol, and stir for 6 hours at room temperature to obtain a yellow suspension. Filter and rinse with ice ethanol to obtain 0.50 g of bright yellow solid powder, with a yield of 76%. 1 HNMR (400MHz, CDCl3): δ8.98(s,2H),8.67(d,J=8.6Hz,1H),8.47(s,1H),8.39(d,J=8.5Hz,1H),8.23(d,J=8.4Hz,1H),8.09–8.07(m ,1H),8.04–8.02(m,1H),7.95(t,J=8.2Hz,2H),7.83–7.79(m,1H),7.67–7.63(m,1H),7.52–7.47(m,3H),7.20(d,J=6.1Hz,2H)ppm. 13 C NMR (100MHz, CDCl3): δ161.12,155.16,148.62,148.24,136.92,132.28,132.19,131.83,130.18,129.98,129.17,12 8.90,128.19,128.01,127.98,127.90,127.34,126.29,125.88,125.61,122.96,119.19,111.74ppm.Anal.Calcdfor C 24 H 16N2:C,86.72;H,4.85;N,8.43.Found:C,87.32;H,4.85;N,7.83.

[0051] Weigh hafnium tetrachloride (0.352g, 1.1mmol), add 10mL dry toluene, slowly add 1.6mL / 4.8mmol methylmagnesium bromide solution (3M) at -40℃ (acetonitrile-liquid nitrogen bath), and stir for 2 hours. Then add ligand (0.332g / 1mmol), stir for 2 hours at -40℃ in dark, and continue to react for 6 hours after returning to room temperature. After the reaction is completed, remove the solvent, extract with toluene, and filter to obtain 0.36g of product with a yield of 63%. 1 H NMR (400MHz, C6D6): δ9.11(s,1H),8.57(d,J=9.6Hz,2H),8.28(s,1H),7.83–7.77(m,3H),7.46–7.37(m,2H),7.37–7 .20(m,2H),7.15–7.04(m,1H),6.63(d,J=8.6Hz,1H),5.37(d,J=6.7Hz,1H),1.26(d,J=6.7Hz,3H),0.64(s,9H)ppm. 13 C NMR (100MHz, C6D6): δ168.76,150.26,142.17,140.41,134.91,132.36,131.85,131.38,130.26,128.93,127.46, 127.39,127.33,126.62,125.63,124.94,124.91,122.95,119.56,116.70,105.71,58.53,22.01ppm.Anal.Calcd for C 28 H 28 HfN2:C,58.89;H,4.94;N,4.91.Found:C,59.42;H,4.51;N,4.81.

[0052] Example 6: C1 catalytic polymerization of propylene

[0053] A 350 mL glass reactor equipped with a magnet was used for the polymerization reaction. 2 μmol of catalyst C1, 2.2 μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate and 100 μmol of methylaluminoxane were weighed in a glove box. The glass reactor was connected to the polymerization pipeline, and when the temperature rose to 80°C, 50 mL of toluene was added thereto. During the polymerization process, propylene gas was continuously introduced to ensure that the reaction pressure was 5 atm. After reacting for 2 minutes, 30 mL of ethanol was added to the reactor under a nitrogen atmosphere. After cooling, the reaction solution was poured into a large amount of ethanol for sedimentation, and the final polymer was obtained by filtration and drying. Polymerization activity: 66320 kg·mol -1 (Hf) h -1 , polymer Mw = 3250 kg·mol -1 , Mw / Mn=2.1.

[0054] Example 7: C1 catalytic polymerization of propylene

[0055] The polymerization process and reaction conditions were the same as in Example 6, and the polymerization temperature was 120° C. Polymerization activity: 42300 kg·mol -1 (Hf) h -1 .Polymer Mw = 2840 kg·mol -1 , Mw / Mn=2.2.

[0056] Example 8: C1 catalytic polymerization of propylene

[0057] A 100mL steel reactor equipped with a magnet was used for polymerization. 50mL of toluene was injected with a syringe, the contents of the reactor were heated to 160°C, and the reactor was saturated with 1Mpa of propylene. 2μmol of catalyst C1, 100μmol of methylaluminoxane, and 2.2μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate were added to the glove box, dissolved in toluene, and transferred to the catalyst storage tube through a syringe, and nitrogen (over 1MPa) was pressed into the reactor. During the polymerization process, ethylene gas was continuously introduced to ensure that the reaction pressure was 1MPa. After reaching the set reaction time of 2min, 2mL of ethanol was pressed into the reactor under nitrogen (over 1MPa), the reactor was cooled and vented, and the contents of the reactor were poured into a large amount of ethanol. The polymer precipitated and filtered to obtain the polymer, which was washed with a small amount of ethanol and finally vacuum dried overnight and weighed. Polymerization activity: 35600kg·mol -1 (Hf) h -1 , polymer Mw = 2230 kg·mol -1 , Mw / Mn=2.4.

[0058] Example 9: C1 catalytic polymerization of propylene

[0059] The polymerization process and reaction conditions were the same as in Example 8, and the polymerization temperature was 180° C. Polymerization activity: 17090 kg·mol -1 (Hf) h -1 . Polymer Mw = 1840 kg·mol -1 , Mw / Mn=2.4.

[0060] Example 10: C1 catalytic polymerization of propylene

[0061] A 350 mL glass reactor equipped with a magnet was used for the polymerization reaction. 2 μmol of catalyst C1, 2.2 μmol of tripentafluorophenyl boron and 100 μmol of methylaluminoxane were weighed in a glove box. The glass reactor was connected to the polymerization pipeline, and when the temperature rose to 120°C, 50 mL of toluene was added thereto. During the polymerization process, propylene gas was continuously introduced to ensure that the reaction pressure was 5 atm. After reacting for 2 minutes, 30 mL of ethanol was added to the reactor under a nitrogen atmosphere. After cooling, the reaction solution was poured into a large amount of ethanol for sedimentation, and the final polymer was obtained by filtration and drying. Polymerization activity: 10600 kg·mol -1 (Hf) h -1 , polymer Mw = 2410 kg·mol -1 , Mw / Mn=1.9.

[0062] Example 11: C1 catalytic polymerization of propylene

[0063] A 350 mL glass reactor equipped with a magnet was used for the polymerization reaction. 2 μmol of catalyst C1 and 1000 μmol of methylaluminoxane were weighed in a glove box. The glass reactor was connected to the polymerization pipeline, and when the temperature rose to 120°C, 50 mL of toluene was added thereto. During the polymerization process, propylene gas was continuously introduced to ensure that the reaction pressure was 5 atm. After reacting for 2 min, 30 mL of ethanol was added to the reactor under a nitrogen atmosphere. After cooling, the reaction solution was poured into a large amount of ethanol for sedimentation, and the final polymer was obtained by filtration and drying. Polymerization activity: 890 kg·mol -1 (Hf) h -1 , polymer Mw = 890 kg·mol -1 , Mw / Mn=2.6.

[0064] Example 12: C2 catalytic polymerization of propylene

[0065] The polymerization process and reaction conditions were the same as in Example 8, and the catalyst used was C2. Polymerization activity: 43250 kg·mol -1 (Hf) h -1 .Polymer Mw = 2450 kg·mol -1 , Mw / Mn=2.0.

[0066] Example 12: C3 catalytic polymerization of propylene

[0067] The polymerization process and reaction conditions were the same as in Example 8, and the catalyst used was C3. Polymerization activity: 14500 kg·mol -1 (Zr)·h -1 .Polymer Mw = 980 kg·mol -1 , Mw / Mn=2.1.

[0068] Example 13: C4 catalytic propylene polymerization

[0069] The polymerization process and reaction conditions were the same as in Example 8, and the catalyst used was C4. Polymerization activity: 34200 kg·mol -1 (Hf) h -1 .Polymer Mw = 1010 kg·mol -1 , Mw / Mn=2.1.

[0070] Example 14: Hf1 catalyzed propylene polymerization

[0071] The polymerization process and reaction conditions were the same as in Example 8, and the catalyst used was Hf1. Polymerization activity: 2450 kg·mol -1 (Hf) h -1 . Polymer Mw = 170 kg·mol -1 , Mw / Mn=2.1.

[0072] Example 15: Hf2-catalyzed propylene polymerization

[0073] The polymerization process and reaction conditions were the same as in Example 8, and the catalyst used was Hf2. Polymerization activity: 8750 kg·mol -1 (Hf) h -1 . Polymer Mw = 520 kg·mol -1 , Mw / Mn=1.9.

[0074] Example 16: Hf3-catalyzed propylene polymerization

[0075] The polymerization process and reaction conditions were the same as in Example 8, and the catalyst used was Hf3. Polymerization activity: 7860 kg·mol -1 (Hf) h -1 . Polymer Mw = 230 kg·mol -1 , Mw / Mn=2.2.

[0076] Example 17: Hf4-catalyzed propylene polymerization

[0077] The polymerization process and reaction conditions were the same as in Example 8, and the catalyst used was Hf4. Polymerization activity: 6980 kg·mol -1(Hf) h -1 . Polymer Mw = 220 kg·mol -1 , Mw / Mn=2.0.

[0078] Example 18: C2 catalyzed ethylene / 1-octene copolymerization

[0079] A 350mL glass reactor equipped with a magnet was used for the polymerization reaction. 2μmol of catalyst C2, 2.2μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate and 100μmol of methylaluminoxane were weighed in a glove box. Then the glass reactor was connected to the polymerization pipeline, and when the temperature rose to 120°C, 26.6mL of toluene and 23.4mL of 1-octene were added thereto. During the polymerization process, ethylene gas was continuously introduced to ensure that the reaction pressure was 5atm. After reacting for 2 minutes, 30mL of ethanol was added to the reactor under a nitrogen atmosphere. After cooling, the reaction solution was poured into a large amount of ethanol for sedimentation, and the final polymer was obtained by filtration and drying. Polymerization activity: 45300kg·mol -1 (Hf) h -1 , polymer Mw = 732 kg·mol -1 , Mw / Mn=2.2, the content of 1-octene in the copolymer is 29.2 mol%.

[0080] Example 19: C2 catalyzed ethylene / 1-octene copolymerization

[0081] The polymerization process and reaction conditions were the same as in Example 18, except that 34.4 mL of toluene and 15.6 mL of 1-octene were used. Polymerization activity: 39400 kg·mol -1 (Hf) h -1 .Polymer Mw = 536 kg·mol -1 , Mw / Mn=2.3, the content of 1-octene in the copolymer is 21.5 mol%.

[0082] Example 20: C2 catalyzed ethylene / 1-octene copolymerization

[0083] The polymerization process and reaction conditions were the same as in Example 18, except that 42.2 mL of toluene and 7.8 mL of 1-octene were used. Polymerization activity: 24900 kg·mol -1 (Hf) h -1 .Polymer Mw = 437 kg·mol -1 , Mw / Mn=2.2, the content of 1-octene in the copolymer is 13.7 mol%.

[0084] Example 21, C2 catalyzed ethylene / 1-octene copolymerization

[0085] A 100 mL steel reactor equipped with a magnet was used for the polymerization reaction. A mixture of 26.6 mL toluene and 23.4 mL 1-octene (50 mL in total) was injected with a syringe. The contents of the reactor were heated to 120°C and the reactor was saturated with 1 MPa ethylene. 2 μmol of catalyst C2, 100 μmol of methylaluminoxane, and 2.2 μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate were added to the glove box, dissolved in toluene, and transferred to the catalyst storage tube through a syringe, and then pressed into the reactor with nitrogen (over 1 MPa). During the polymerization process, the reaction pressure was ensured to be 1 MPa by continuously introducing ethylene gas. After reaching the set reaction time of 2 min, 2 mL of ethanol was pressed into the reactor under nitrogen (over 1 MPa), the reactor was cooled and vented, and the contents of the reactor were poured into a large amount of ethanol. The polymer precipitated and filtered to obtain the polymer, which was washed with a small amount of ethanol and finally vacuum dried overnight and weighed. Polymerization activity: 38900 kg·mol -1 (Hf) h -1 , polymer Mw = 492 kg·mol -1 , Mw / Mn=2.1, the content of 1-octene in the copolymer is 9.8 mol%.

[0086] Example 22: C2 catalyzed ethylene / 1-octene copolymerization

[0087] The polymerization process and reaction conditions were the same as in Example 21, and the polymerization pressure was 2 MPa. Polymerization activity: 43700 kg·mol -1 (Hf) h -1 . Polymer Mw = 541 kg·mol -1 , Mw / Mn=2.1, the content of 1-octene in the copolymer is 6.5 mol%.

[0088] Example 23: C2 catalyzed ethylene / 1-octene copolymerization

[0089] The polymerization process and reaction conditions were the same as in Example 21, and the polymerization pressure was 3 MPa. Polymerization activity: 55600 kg·mol -1 (Hf) h -1 . Polymer Mw = 568 kg·mol -1 , Mw / Mn=2.0, the content of 1-octene in the copolymer is 4.8 mol%.

[0090] Example 24: C2 catalyzed ethylene / 1-octene copolymerization

[0091] The polymerization process and reaction conditions were the same as in Example 21, and the selected temperature was 140°C. Polymerization activity: 32500 kg·mol -1 (Hf) h -1 , polymer Mw = 492 kg·mol-1 , Mw / Mn=2.1, the content of 1-octene in the copolymer is 23.4 mol%.

[0092] Example 25: C2 catalyzed ethylene / 1-octene copolymerization

[0093] The polymerization process and reaction conditions were the same as in Example 21, and the selected temperature was 160° C. Polymerization activity: 22450 kg·mol -1 (Hf) h -1 . Polymer Mw = 431 kg·mol -1 , Mw / Mn=2.3, the content of 1-octene in the copolymer is 25.6 mol%.

[0094] Example 26: C1 catalyzed ethylene / 1-octene copolymerization

[0095] The polymerization process and reaction conditions were the same as in Example 21, and the catalyst used was C1. Polymerization activity: 65600 kg·mol -1 (Hf) h -1 .Polymer Mw = 824 kg·mol -1 , Mw / Mn=2.1, the content of 1-octene in the copolymer is 18.8 mol%.

[0096] Example 27: C3 catalyzed ethylene / 1-octene copolymerization

[0097] The polymerization process and reaction conditions were the same as in Example 21, and the catalyst used was C3. Polymerization activity: 15400 kg·mol -1 (Hf) h -1 .Polymer Mw = 266 kg·mol -1 , Mw / Mn=2.3, the content of 1-octene in the copolymer is 15.9 mol%.

[0098] Example 28: C4 catalyzed ethylene / 1-octene copolymerization

[0099] The polymerization process and reaction conditions were the same as in Example 21, and the catalyst used was C4. Polymerization activity: 49800 kg·mol -1 (Hf) h -1 .Polymer Mw = 925 kg·mol -1 , Mw / Mn=2.2, the content of 1-octene in the copolymer is 12.3 mol%.

[0100] Example 29: C2 catalyzed ethylene / 1-hexene copolymerization

[0101] A 350mL glass reactor equipped with a magnet was used for the polymerization reaction. 2μmol of catalyst C2, 2.2μmol of triphenyl carbon tetrakis (pentafluorophenyl) borate and 100μmol of methylaluminoxane were weighed in a glove box. Then the glass reactor was connected to the polymerization pipeline, and when the temperature rose to 120°C, 31.6mL of toluene and 18.4mL of 1-hexene were added thereto. During the polymerization process, ethylene gas was continuously introduced to ensure that the reaction pressure was 5atm. After reacting for 2 minutes, 30mL of ethanol was added to the reactor under a nitrogen atmosphere. After cooling, the reaction solution was poured into a large amount of ethanol for sedimentation, and the final polymer was obtained by filtration and drying. Polymerization activity: 62500kg·mol -1 (Hf) h -1 , polymer Mw = 773 kg·mol -1 , Mw / Mn=2.0, the content of 1-hexene in the copolymer is 24.7 mol%.

[0102] Example 30: Hf1-catalyzed ethylene / 1-hexene copolymerization

[0103] The polymerization process and reaction conditions were the same as in Example 29, and the catalyst used was Hf1. Polymerization activity: 42130 kg·mol -1 (Hf) h -1 . Polymer Mw = 180 kg·mol -1 , Mw / Mn=2.2, the content of 1-hexene in the copolymer is 18.6 mol%.

[0104] Example 31: Hf2-catalyzed ethylene / 1-hexene copolymerization

[0105] The polymerization process and reaction conditions were the same as in Example 29, and the catalyst used was Hf2. Polymerization activity: 39800 kg·mol -1 (Hf) h -1 .Polymer Mw = 284 kg·mol -1 , Mw / Mn=2.7, the content of 1-hexene in the copolymer is 22.4 mol%.

[0106] Example 28: Hf3-catalyzed ethylene / 1-hexene copolymerization

[0107] The polymerization process and reaction conditions were the same as in Example 29, and the catalyst used was Hf3. Polymerization activity: 47800 kg·mol -1 (Hf) h -1 .Polymer Mw = 187 kg·mol -1 , Mw / Mn=2.1, the content of 1-hexene in the copolymer is 14.9 mol%.

[0108] Example 29: Hf4-catalyzed ethylene / 1-hexene copolymerization

[0109] The polymerization process and reaction conditions were the same as in Example 29, and the catalyst used was Hf4. Polymerization activity: 17300 kg·mol -1 (Hf) h -1 . Polymer Mw = 223 kg·mol -1 , Mw / Mn=2.1, the content of 1-hexene in the copolymer is 11.2 mol%.

Claims

1. A quinoline amine binuclear metal titanium zirconium hafnium catalyst, the structure of which is shown in formula (I): in, M is selected from titanium, zirconium, and hafnium; R 1 -R 4 , R 1’ -R 4’ Each independently selected from hydrogen, C1-C 20 Alkyl, C1-C 20 Alkoxy, C6-C 20 Aryl, C6-C 20 Aralkyl, or any two adjacent carbon atoms of phenyl and the surrounding substituents form a ring containing 4-20 carbon atoms; R 1’ -R 4’ R 1 -R 4 Same or Different; R 5 , R 5’ Each is independently selected from a C1-C6 straight chain alkyl group, a tert-butyl group, a phenyl group, a benzyl group, or an isopropylphenyl group.

2. The preparation method of the quinolineamine binuclear titanium zirconium hafnium catalyst according to claim 1 comprises the following steps: dissolving the metal salt in 20-80 mL of anhydrous solvent under a nitrogen atmosphere, adding 4.0-5.0 molar equivalents of methyl magnesium bromide, reacting at -40°C to -20°C for 2-6 hours, then adding 0.5 molar equivalents of a bifunctional quinolineamine ligand, reacting at -40°C to -20°C for 2-6 hours, then warming to room temperature and reacting for 2-12 hours; after the reaction is completed, removing the solvent under reduced pressure, and extracting with a good solvent to obtain the quinolineamine binuclear titanium zirconium hafnium catalyst according to claim 1.

3. The preparation method according to claim 2, characterized in that: The anhydrous solvent is selected from toluene, n-hexane, xylene, and benzene; the good solvent is selected from n-hexane, toluene, pentane, heptane, and cyclohexane.

4. The preparation method according to claim 2, characterized in that: The metal salt is selected from one of TiCl4, ZrCl4 and HfCl4.

5. A method for olefin polymerization, characterized in that: The catalyst used is the quinolineamino binuclear metal titanium zirconium hafnium catalyst described in claim 1.

6. The method according to claim 5, characterized in that: The olefin monomer is one or more of ethylene, propylene, 1-butene, styrene, 1-hexene, 1-octene and 1-decene.

7. The method according to claim 5, characterized in that: The quinolineamine-based binuclear metal titanium zirconium hafnium catalyst needs to be coordinated with a co-catalyst for catalysis, and the co-catalyst is one or more of trispentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, aluminoxane, alkyl aluminum, and alkyl aluminum chloride.

8. The method according to claim 7, characterized in that: The aluminoxane is methylaluminoxane, ethylaluminoxane or isobutylaluminoxane; the alkylaluminum is trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; and the alkylaluminum chloride is diethylaluminum monochloride, diethylaluminum sesquichloride or ethylaluminum dichloride.

9. The method according to claim 5, characterized in that: The polymerization temperature is 0-200° C., the polymerization pressure is 0.1-5 MPa, the molar ratio of the catalyst to the co-catalyst is 1:(1-5000), the reaction time is 0.1-48 hours, and the polymerization solvent is one or more of n-hexane, n-heptane, n-pentane, and toluene.

Citation Information

Cited By

  • Propenyl block polyolefin elastomer and preparation method thereof

    CN121851292A